Islamic perspective on conceptualization and normative analysis of euthanasia - Malik, Mohammad Manzoor (s.n, 2012)
Euthanasia is usually understood in several senses; it is sometimes understood as intentional killing of terminally ill patients, suicide, physician assisted suicide, and passive euthanasia. The research by analysis and criticism of euthanasia restricts its meaning to narrow construal of euthanasia or active euthanasia